The Nutrition MDG Indicator : Interpreting Progress - Chhabra, Ritu; Rokx, Claudia (World Bank, Washington, DC, 2013)
This paper argues for more nuance in the interpretation of progress towards the Nutrition Millennium Development Goal indicator (halving the prevalence of underweight children, under 5 years old, by 2015). Interpretation of a country's performance based on trends alone is ambiguous, and can lead to erroneous prioritization of countries in need of donor assistance. For instance, a country may halve the prevalence by 2015, but will still have unacceptable high malnutrition rates. This paper analyses which countries are showing satisfactory and unsatisfactory progress using the Annual Rate of Change (ARC), and then introduces the World Health Organization-classification of severity of malnutrition in the analysis to provide more nuance. It highlights that a little less than half of the Bank's client population is likely to halve underweight by 2015. Although the paper uses national data only, it flags the risks and recommends that countries take regional disparities into their needs-analysis. The paper also argues for more attention to the other important nutrition indicators, stunting and micronutrient deficiencies, which remain enormous problems, and briefly discusses solutions to reducing underweight malnutrition.